Fungal microsomes in a biotransformation perspective: protein nature of membrane-associated reactions - Svobodová, Kateřina; Mikesková, Hana; Petráčková, Denisa (Applied microbiology and biotechnology, 2013)
Microsomal fraction of fungal cells grabs the attention of many researchers for it contains enzymes that play a role in biotechnologically relevant processes. Microsomal enzymes, namely, CYP450s, were shown to metabolize a wide range of xenobiotic compounds, including PAHs, PCBs, dioxins, and endocrine disruptors, and take part in other fungal biotransformation reactions. However, little is known about the nature and regulation of these membrane-associated reactions. Advanced proteomic and post-genomic techniques make it possible to identify larger numbers of microsomal proteins and thus add to a deeper study of fungal intracellular processes. In this work, proteins that were identified through a shotgun proteomic approach in fungal microsomes under various culture conditions are reviewed. However, further research is still needed to fully understand the role of microsomes in fungal biodegradation and biotransformation reactions.
Keywords: houby; Microsomes; proteomika; Fungi; biotransformace; membránové proteiny; mikrozomy; Membrane Proteins; Proteomics; Biotransformation; intracelulární membrány; Intracellular Membranes